2006
DOI: 10.1093/jn/136.7.1855
|View full text |Cite
|
Sign up to set email alerts
|

A Reduced Carbohydrate, Increased Protein Diet Stabilizes Glycemic Control and Minimizes Adipose Tissue Glucose Disposal in Rats

Abstract: The dietary reference intakes (DRIs) established an acceptable macronutrient distribution range (AMDR); however, few studies have evaluated differences in metabolic regulations across the DRI range. This study examined differences in glycemic regulations associated with specific ratios of carbohydrate and protein. Male rats ( approximately 200 g) were fed either a high-carbohydrate diet (CHO group: 60% of energy as carbohydrates, 12% protein, 28% fat) or a reduced-carbohydrate diet [PRO (protein) group: 42% ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
30
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 28 publications
6
30
0
Order By: Relevance
“…This pathway could participate in coping with amino acid excess in high-protein fed rats. In HP rats, the fed state was characterized by high hepatic glycogen levels, equivalent to those found in NP fed rats, in agreement with the findings of other studies (3,45,52). Moreover, we found that glucose release from isolated hepatocytes is very low and is not different between NP-and HP-fed rats.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This pathway could participate in coping with amino acid excess in high-protein fed rats. In HP rats, the fed state was characterized by high hepatic glycogen levels, equivalent to those found in NP fed rats, in agreement with the findings of other studies (3,45,52). Moreover, we found that glucose release from isolated hepatocytes is very low and is not different between NP-and HP-fed rats.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies had reported a postprandial secretion of both insulin and glucagon in rats fed a HP diet (3,18). In that context, the respective influence of amino acids and insulin on glucagoninduced PEPCK and G6PC1 gene expression was investigated in vitro in primary cultures of isolated hepatocytes with constant concentration of glucose (5.5 mM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the plasma levels of other amino acids may also change in obesity, the rises in the BCAAs are of particular interest because they appear to have unique obesity-related effects. Indeed, it has been posited that BCAAs may be responsible for some of the beneficial effects of high-protein diets, improving body weight control and adiposity (1,9,18,29,30,39). Similarly, BCAAs improve muscle glucose uptake, whole body glucose metabolism, and oxidation (7,8,43).…”
mentioning
confidence: 99%
“…Plasma insulin levels also increase in response to consumption of a high-protein meal, although the magnitude of the response is less compared with carbohydrate alone (2,3,16,30). However, in contrast to a high-carbohydrate meal, plasma glucagon levels increase rather than decrease in response to a high-protein meal (2,3,16,30). Based on the results of the present study, it might therefore be expected that mTORC1 signaling would be repressed in the liver after consumption of a high-protein meal.…”
Section: Discussionmentioning
confidence: 99%